Financial Factors Affecting Tax Aggressiveness in JII70 Companies - Riska Ainur Rosyida; Chairil Anwar; Achmad Wicaksono; Kafidin Muzakki (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Taxation is the primary source of government revenue used to finance national development. However, companies’ efforts to reduce their tax burden may lower government revenue and affect the sustainability of development. Specific Background: Tax aggressiveness can be influenced by financial conditions, including profitability, liquidity and leverage. This issue is also relevant to Sharia-compliant companies listed on the Jakarta Islamic Index 70 (JII70), which have undergone a Sharia screening process regulated by the Financial Services Authority (OJK). Knowledge Gap: Studies on tax aggressiveness amongst Sharia-compliant companies remain limited and report inconsistent findings, whilst previous research has largely focused on non-Sharia-compliant companies. Objective: This study examines the influence of profitability, liquidity and leverage on tax aggressiveness amongst JII70 companies during the period 2021–2024. Methods: A quantitative approach was employed, utilising secondary data, purposive sampling, and multiple linear regression analysis on 38 companies (152 observations). Results: Profitability did not have a significant effect on tax aggressiveness, whilst liquidity and leverage had significant negative effects; collectively, all these variables significantly influenced tax aggressiveness. Novelty: This study provides empirical evidence from JII70 companies, a research context that has been relatively unexplored. Implications: These findings provide insights for companies, investors and regulators in decision-making and oversight relating to taxation.